Analysis of Conformational Preferences in Caffeine (2022)
ABSTRACT: High level DLPNO–CCSD(T) electronic structure calculations with extended basis sets over B3LYP–D3 optimized geometries indicate that the three methyl groups in caffeine overcome steric hindrance to adopt uncommon conformations, each one placing a C–H bond on the same plane of the aromatic system, leading to the C–H bonds eclipsing one carbonyl group, one heavily delocalized C–N bond constituent of the fused double ring aromatic system, and one C–H bond from the imidazole ring. Deletion of indiscriminate and selective non-Lewis orbitals unequivocally show that hyperconjugation in the form of a bidirectional –CH3 aromatic system charge transfer is responsible for these puzzling conformations. The structural preferences in caffeine are exclusively determined by orbital interactions, ruling out electrostatics, induction, bond critical points, and redistribution because the steric effect, the allylic effect, the Quantum Theory of Atoms in Molecules (QTAIM), and the non-covalent interactions (NCI), all predict wrong energetic orderings. Tiny rotational barriers, not exceeding 1.3 kcal/mol suggest that at room conditions, each methyl group either acts as a free rotor or adopts fluxional behavior, thus preventing accurate determination of their conformations. In this context, our results supersede current experimental ambiguity in the assignation of methyl conformation in caffeine and, more generally, in methylated xanthines and their derivatives.